291 Virtual Classroom Proficiency-Based Progression for Robotic Surgery Training (VROBOT): A Prospective, Cross-Over, Effectiveness Study. (19th August 2022) - Nathan, Arjun; Patel, Sonam; Georgi, Maria; Mullins, Will; Fricker, Monty; Asif, Aqua; Ng, Alexander; Hang, Man Kien; Light, Alexander; Francis, Nader; Kelly, John; Collins, Justin; et al.
Abstract: Aim: Robotic surgical training has historically lacked evidence-based standardisation. The Fundamentals of Robotic Surgery (FRS) curriculum addresses this by incorporating proficiency-based modules which certify trainees' skills. However, the curriculum is self-directed and non-interactive. We aim to determine the effectiveness of interactive virtual classroom training (VCT) as an adjunct to the FRS curriculum for robotic skills training. Method: 11 novice surgical trainees were randomly allocated to two groups. Both groups completed a one-week robotic skills induction. In week two, Group A received training with the FRS curriculum and adjunctive VCT; Group B only received access to the FRS curriculum. In week three, the groups received the alternate intervention. The primary outcome was measured using the validated robotic-objective structured assessment of technical skills (R-OSAT). Results: 11 participants completed the training curriculum; all were included in analyses. Both groups demonstrated significantly improved proficiency upon completion of the training. At time point 1 (end of week two) Group A achieved a statistically significant greater mean proficiency score compared to Group B (44.80 vs 35.33 points, p=0.006). At time point 2 (end of week three), there was no significant difference in Group A's mean score from time point 1. In contrast, Group B showed significant improvement in mean proficiency by 9.67 points from time point 1 (95% CI 5.18–14.15, p=0.003). Conclusions: VCT is an effective training adjunct to the FRS curriculum for the learning of basic robotic skills. With the steep learning curve in robotic surgery training, VCT offers interactive learning and can increase training effectiveness.